"Mistakes Made by Students in the Study of Legal English and How to Avoid Them" - Marfuakhon Akhmedova (Periodica Journal, 2024)
The article examines the most common mistakes students encounter when learning legal English and offers strategies for addressing them. Focusing on grammatical, syntactical, and terminological challenges, it explores translation issues, intercultural differences, and stylistic inconsistencies. Practical recommendations include using glossaries, analyzing legal texts, and employing interactive teaching techniques. Key exercises and methods for improving grammar, style, and terminology are presented to help students overcome these difficulties effectively
Keywords: Legal English; legal terminology; grammatical errors